2018
DOI: 10.3390/ma11112290
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Magnetic and Microstructural Characterization of Wear Progress on Case-Hardened 16MnCr5 Gear Wheels

Abstract: The evaluation of wear progress of gear tooth flanks made of 16MnCr5 was performed using non-destructive micro-magnetic testing, specifically Barkhausen noise (BN) and incremental permeability (IP). Based on the physical interaction of the microstructure with the magnetic field, the micro-magnetic characterization allowed the analysis of changes of microstructure caused by wear, including phase transformation and development of residual stresses. Due to wide parameter variation and application of bandpass filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Magnetic Barkhausen noise (MBN) is a promising non-destructive technique that could be potentially adapted for fast and reliable surface monitoring. An increasing number of studies can now be found in which MBN is investigated as a function stress state [ 1 , 2 , 3 , 4 ], dislocation density [ 5 , 6 ], carbides or nitrides size and distribution [ 7 , 8 ], presence of non-ferromagnetic phases [ 9 ], etc. However, this technique is most widely employed for monitoring ground surfaces in real industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Barkhausen noise (MBN) is a promising non-destructive technique that could be potentially adapted for fast and reliable surface monitoring. An increasing number of studies can now be found in which MBN is investigated as a function stress state [ 1 , 2 , 3 , 4 ], dislocation density [ 5 , 6 ], carbides or nitrides size and distribution [ 7 , 8 ], presence of non-ferromagnetic phases [ 9 ], etc. However, this technique is most widely employed for monitoring ground surfaces in real industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Domain walls are pinned by dislocation tangles, precipitates, grain boundaries, non-ferromagnetic particles, or phases, etc. [18,19,20,21]. On the other hand, the stress state strongly affects the domain walls’ alignment.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental setup of this contribution the MBN measurements were performed with an excitation frequency of f M = 300 Hz with an amplitude of U = 0.573 V. The research question whether this configuration leads to an optimal correlation between the resulting MBN signal of this specific material and the hardness of the material is, albeit important for future research, out of the scope of this contribution. The depth of the MBN analysis is especially dependent on the used excitation frequency due to the skin effect [24]. Thus, higher excitation frequencies lead to analysis closer to the material surface.…”
Section: Dataset Generation: Magnetic Barkhausen Noise Measurement Anmentioning
confidence: 99%